Book Review of Nicholas Sparks’s The Last Song - Listiani, Nia Putri (LANTERN (Journal on English Language, Culture and Literature), 2015)
Novel that became a study in this final project is the last song titled essay writer from United States, Nicholas Sparks. This novel tells the story of love and affection between a daughter and her father who was not good at beginning. The writer uses to read carefully to find the message in the book which contained many elements of learning. Authors describe the theme, the advantages and disadvantages from novel The Last Song. This novel have a main theme of father and daughter as well and minor story of teen romance.The main advantage of this novel on the theme is life that should valuable, trust and confidence, to forgive and be mature, passionate main character especially in music and love. However, not only the theme, but the author used words that are easy to understand, and easy to explain the characters in the novel. The lacked only drawback of the book's appearance does not match with the content of the novel. This is what underlies the writer to review the strengths and the weaknesses of The Last Song novel and the reader will get a general overview, and a reference to reader.Keywords : Family Love, Daughter – Father Relationship, Romance, The Strength, The